A multi-source data collection and information fusion method for distribution network based on IOT protocol. Issue 2 (February 2021) - Cai, Yongxiang; Xiao, Xiaobing; Tian, Hao; Fu, Yu; Wu, Peng; He, Hongliu
Abstract: With the construction of Global Energy Internet, Intelligent distribution network has more and more characteristics of multi scene, multi service and changeable measurement and control objects. In order to realize data collection and information exchange among the intelligent terminal and energy, power grid, load, energy storage and other control resources in distribution network, we should research an architecture which can adapt to various data sources Based on dynamic self describing protocol.